Austria : 2021 Article IV Consultation-Press Release; Staff Report; Staff Supplementary Information; and Statement by the Executive Director for Austria. (IMF Staff Country Reports; Country Report ;, 2021)
Austria entered the crisis from a strong position. Prudent policies prior to the pandemic provided significant policy space. Several lockdowns helped contain the virus but significantly impaired the economy. Real GDP contracted by 6.3 percent in 2020 and declined further in early 2021. The 2021 recovery is expected to be modest; the tourism and hospitality sectors will continue to be affected. Over the medium term, growth will accelerate in 2022 and then stabilize at potential, but the output level will remain somewhat below the pre-COVID trend. Uncertainty remains high.